"Biological Adhesion" is a Significantly Regulated Molecular Process during Long-Term Primary In Vitro Culture of Oviductal Epithelial Cells (Oecs): A Transcriptomic and Proteomic Study - Budna-Tukan, Joanna; Światły-Błaszkiewicz, Agata; Celichowski, Piotr; Kałużna, Sandra; Konwerska, Aneta; Sujka-Kordowska, Patrycja; Jankowski, Maurycy; Kulus, Magdalena; Jeseta, Michal; Piotrowska-Kempisty, Hanna; Józkowiak, Małgorzata; Antosik, Paweł; et al. (International journal of molecular sciences, 2019)
Oviductal epithelial cells (OECs) actively produce stimulating and protecting factors, favoring survival and viability of gametes and early embryos. The oviduct participates in the initial reproductive events, which strongly depends on adhesion. The analysis of differential gene expression in OECs, during long-term in vitro culture, enables recognition of new molecular markers regulating several processes, including "biological adhesion". Porcine oviducts were stained with hematoxylin and eosin, as well as with antibodies against epithelial markers. Then, OECs were long-term in vitro cultured and after 24 h, 7, 15, and 30 days of culture were subjected to transcriptomic and proteomic assays. Microarrays were employed to evaluate gene expression, with Matrix-assisted laser desorption/ionization-time of light (MALDI-TOF) mass spectrometry applied to determine the proteome. The results revealed proper morphology of the oviducts and typical epithelial structure of OECs during the culture. From the set of differentially expressed genes (DEGs), we have selected the 130 that encoded proteins detected by MALDI-TOF MS analysis. From this gene pool, 18 significantly enriched gene ontology biological processes (GO BP) terms were extracted. Among them we focused on genes belonging to "biological adhesion" GO BP. It is suggested that increased expression of studied genes can be attributed to the process of intensive secretion of substances that exhibit favorable influence on oviductal environment, which prime gametes adhesion and viability, fertilization, and early embryo journey.
Keywords: Fallopian Tubes; kultivované buňky; epitelové buňky; Oviducts; biological adhesion; Gene Expression Profiling; proteomika; výpočetní biologie; transkriptom; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Epithelial Cells; sliznice; Transcriptome; pig; Cells, Cultured; Swine; oviductal epithelial cells; Proteomics; ženské pohlaví; Mucous Membrane; Proteome; zvířata; Tandem Mass Spectrometry; microarray; vejcovody u zvířat; spektrometrie hmotnostní - ionizace laserem za účasti matrice; prasata; stanovení celkové genové exprese; tandemová hmotnostní spektrometrie; mass spectrometry; proteom; Computational Biology; Female; vejcovody; Animals